Women and Leadership: Selection, Development, Leadership Style, and Performance. (March 2017) - Gipson, Asha N.; Pfaff, Danielle L.; Mendelsohn, David B.; Catenacci, Lauren T.; Burke, W. Warner
Despite the proliferation of leadership research in the past 75 years, investigating the ways in which women and men leaders enact and experience leadership continues to surface unanswered questions. Through the framework of selection, development, leadership style, and performance, we report gender-related findings from a broad survey of existing literature from the past three decades. Findings include differential rates of selection for women and men leaders; leader development considerations that vary by gender; evidence in favor of general similarities in leadership style (with noted exceptions) between women and men leaders; and similar performance outcomes between women and men leaders. The importance of context, be it job type, group composition, organizational culture, or industry/sector, was also revealed. Implications for practitioners and academics alike are offered throughout this report.